OC-032 Type 2 Diabetes and Obesity will Drive the Burden of Liver Cirrhosis in the Next Two Decades. (17th August 2016) - Harris, R; Delahooke, T; Card, TR; Guha, IN; Aithal, GP
Abstract : Introduction: Over the past 30 years excessive alcohol consumption has been identified as the predominant risk factor underlying the striking rise in standardised mortality rates from liver disease in the UK. However, with the increasing incidence of type 2 diabetes and obesity within the general population, the risk factor profile associated with cirrhosis may change. Aim: To estimate the prevalence of clinically significant chronic liver disease amongst adults in a primary care population and identify the impact of different risk factors. Methods: Asymptomatic adult patients from a primary care practice covering a population of 4600 in inner city Leicester were screened for risk factors including (1) a diagnosis of type 2 diabetes (2) a raised body mass index (BMI) of ≥27.3 kg/m 2 and (3) hazardous alcohol use. All of those with one or more of risk factors were invited to undergo a liver stiffness measurement using transient elastography (TE). A TE threshold of ≥8 kPa was used to make a diagnosis of clinically significant liver disease. 1 Results: Of the 1320 patients identified with risk factors, 705 underwent TE and 82 had an increased liver stiffness measurement of ≥8 kPa (Table 1 ). Of those patients with hazardous alcohol use as the only risk factor, 3.5 [95% CI 0.73–9.8]% had raised liver stiffness when compared to 7.9 [95% CI 2.9–16.4]% of patients with type 2 diabetes or 8.6% [95% CI 6–11.9]% with a raised BMI. Overall 16/82 (19.5%) patients had hazardous alcohol use (with or without type 2 diabetes and a raised BMI) as a risk factor for an elevated liver stiffness measurment compared to 66/82 (80.5%) with type 2 diabetes and/or a raised BMI (without hazardous alcohol use). Conclusion: In the primary care population that was screened for major risk factors of chronic liver disease, a raised BMI and type 2 diabetes accounted for over 80% of those with clinically significant chronic liver disease. Population based interventions are urgently required to address obesity and type 2 diabetes which are likely to contribute to the burden of cirrhosis in the next decade. Reference: 1 Roulot D, et al . Transient elastography as a screening tool for liver fibrosis and cirrhosis in a community-based population aged over 45 years. Gut 2011;60 (7):977–84. Disclosure of Interest: None Declared